Multiple Membership and Regional Economic Integration in Africa (African Journal of Law and Politics, 2023)
In recent times there has been a proliferation of Regional Economic organizations in Africa. The multiplicity of belonging by many African countries can be challenging or can serve as a catalyst to regional integration. This is because there is diversity and differences regarding history, legal text, economic and political systems. From this premise this Article describes and evaluates the effects of multiple memberships on regional economic integration in Africa. In order to accomplish this, the legal approach was adopted through documentary and textual analysis. This article illustrates the Manifestations of Multiple Memberships of Regional Economic Integration in Africa, discusses an overlay of ECOWAS, WAEMU and CEMAC Countries, the criss-crossing amongst Eastern and Southern African Regions, the multiple membership tendencies within OHADA and finally constraints to regional economic integration in Africa. The Article concludes that the effects of the spaghetti membership are more negative than positive. It is observed that a large percentage of the African populace is mired in poverty while the sub-continent continues to be marginalized in global affairs. The obvious reality is that Africa is yet to benefit fully from the gains of regional economic integration as Regionalism in Africa raises several issues of contradictions. It recommends that measures and policies should be taken to enhance complementarity of memberships in regional organizations and mitigate contradictions through harmonization of rules in order to guarantee real regional economic Integration.